Analysis of mitochondrial cytochrome oxidase I (COI) gene and microsatellites for genetic characterization of grey eel-tail catfish (Plotosus canius Hamilton) in Malaysia - Khalilisamani, Nima (2015)
Plotosus canius (Hamilton, 1822), commonly known as grey eel-tail catfish or locally known as ikan sembilang or semilang, in Malay, is an important marine species in Malaysia, normally consumed as food fish. However, genetic information on the population structure, stock identification and phylogenetic relationship among P.canius populations are still lacking, which could have negative implications on their sustainable conservation and fisheries management throughout Malaysian coastal waters. Therefore, this study was conducted to characterize the genetic structure of P.canius in Malaysia by utilizing the mitochondrial Cytochrome c Oxidase I (COi) gene fragment and a set of five microsatellites loci derived from the Australian freshwater eel-tail catfish (Tandanus tandanus). In order to fulfill the requirement of the present study, a total of 130 samples of P. canius were collected across five selected populations throughout the coastal area of Malaysia. To conduct the COi analysis, a partial fragment (655 bp) of the mitochondrial COi gene, also known as barcoding gene, was sequenced, while five microsatellites loci were selected from the cross species amplification studies originally developed from T.tandanus. Subsequently, associate statistical applications were performed to estimate and infer their phylogenetic relationship, genetic variability and population structure. The experimental and statistic results of the mitochondrial COi analysis revealed that the haplotype diversity varied from 0.395 to 0.771 and nucleotide diversity ranged from 0.033 to 0.65, which pointed out the improbability of mutation effects on gene flow. Moreover, the interesting finding of this study was the sharing of common haplotype KR086940 between populations of Selangor and Johor of Peninsular Malaysia with the Sarawak population of Borneo. This scenario likely reflects a historical genetic connectivity between Peninsular Malaysia and Borneo populations due to the geological history of Southeast Asia during Pleistocene era. Nevertheless, the high pairwise Fsr rates (0.05417 - 0.62504) and consequently high genetic variations among P.canius populations in Peninsular Malaysia and their relatives in Borneo suggested the absence of contemporary gene flow among the current populations. Phylogenetic and Fsr analyses clearly resolved the genetic relationships between P.canius and P.lineatus, supporting their status as distinct species, while all P.canius sequences were diagnosed as belonging to a single species. Microsatellites results show a considerable heterozygote insufficiency in all populations, with the average observed heterozygosity (Ho) value of 0.2168, which was lower than the standard heterozygosity in marine population (Ho= 0.79). This alongside the high Fis values estimation, high pairwise differentiation among populations and low within population variations might be related to several factors such as small sample size, inbreeding and/or non-random mating system. Besides, the discrepancies between the mitochondrial COi and nuclear microsatellites results found in this study pointed towards the sensibility of mitochondrial DNA in detection of variation. In conclusion, the current study has managed to provide a better understanding on the genetic characterization, molecular phylogeny, evolutionary kinship, and population structure in genus Plotosus, in general, and P.canius, in particular. Future studies should encompassed more geographical and sampling sites, larger population sizes per site, and utilization of more mitochondrial and nuclear hypervariable markers. Finally, the results of this study should be necessary highlighted for appropriate fisheries management and conservation of P.canius in Malaysia.